2018
DOI: 10.1111/ans.14494
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leaks in stage IV colorectal cancer

Abstract: Metastatic disease was associated with an increased risk of anastomotic leak and a higher peri-operative mortality rate after colorectal resections for cancer. Patients with anastomotic leaks had a higher peri-operative mortality rate, but long-term survival was unaffected beyond the peri-operative phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
5
1
1
Order By: Relevance
“…We did not find any increase in AL among patients with stage IV rectal cancer treated with RT and operated with AR, even though some retrospective data in the literature suggest such an increase [29]. However, there was an increased risk for AL (OR, 8.72) in patients with stage IV rectal cancer who had been previously treated with RT for prostate cancer, even though this is probably a highly selective group of patients.…”
Section: Discussioncontrasting
confidence: 76%
“…We did not find any increase in AL among patients with stage IV rectal cancer treated with RT and operated with AR, even though some retrospective data in the literature suggest such an increase [29]. However, there was an increased risk for AL (OR, 8.72) in patients with stage IV rectal cancer who had been previously treated with RT for prostate cancer, even though this is probably a highly selective group of patients.…”
Section: Discussioncontrasting
confidence: 76%
“…Several studies examined the impact of the disease stage at the time of surgery on the occurrence of AL, with somewhat inconsistent results 11,[15][16][17][18] . While Bakker et al 11 showed no influence of the disease stage on the occurrence of AL, Ng et al 16 report a threefold, and Kaser et al 17 even fourfold increase in the likelihood of AL in patients with metastatic disease at the time of surgery. In our study, histologic grade of tumor 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cancer stage was not included in the analysis, though several studies have demonstrated the negative impact of stage IV disease on ALs and overall morbidity. 38 Also, the NSQIP mortality data did not include the cause of death. Mortality in AL patients was assumed to be secondary to overwhelming sepsis or an event secondary to an overall proinflammatory state, causing potential misclassification bias in our failure to rescue analysis.…”
Section: Discussionmentioning
confidence: 99%